Analysis of Changes over Time in Four Provisioning Ecosystem Services in Italy - Boschetto, R. G.; Capriolo, A.; Mascolo, R. A.; Arrigotti, J.; Racevich, S.; Bulckaen, A.; Balbi, S.; Villa, F. (Journal of Environmental Accounting and Management, 2026)
Ecosystem service assessment and accounting can offer a valuable approach for linking human activity and nature along with arguments for the conservation and restoration of natural ecosystems. This paper presents an analysis of four provisioning ecosystem services flows at national level: wood biomass provision, crop provision, fish biomass provision and water provision. The methodology applied for the assessment and accounts of each ecosystem service depends on the nature of the service and on data availability. Wood provision is based on fast track approach using data derived from economic aggregates. Crop and fish biomass provision accounts are based on official statistics on yield production. Here, we combine yield statistics with a novel approach to disentangle the yield generated by the ecosystem from what is generated by the human inputs (i.e., planting, chemical products, aquaculture). Water provision is based on a spatial hydrological balance model. Supply and use accounting tables have been developed for the four ecosystem services in line with the United Nations System of Environmental Economic Accounting (UN-SEEA) guidelines and Experimental Ecosystem Accounting (EEA) initiative. The results of this study provide an estimation of the functioning of the ecosystem over time (2012-2018): they help showing the direction of change in ecological and economic terms and the order of magnitude of this change rather than the exact value of Nature (namely ecosystem services). Notwithstanding this study has the merit of being the first exercise of its kind at national level on these specific ecosystem services, it points out the need for further research and in-depth analysis, both to improve the quality of the outcomes and for a better understanding of the estimates meaning.